Students' perceptions of mobile apps: A needs analysis of EFL learners - Nurwahida Nurwahida (Institut Parahikma Indonesia, 2020)
In the current digital age, mobile apps are increasingly being employed to expedite the learning process. However, in order to incorporate mobile apps effectively into classrooms, EFL teachers must first be aware of the logistics of applying mobile apps. The purpose of this research was to investigate the current use of mobile technology in studying English and make recommendations for choosing apps for English learners in EFL contexts. There were 32 students of English Education department chosen as the sample for this study. The data were gathered through semi-structured interviews and questionnaires to find out their perceptions about the use of mobile apps and its current use in the classroom. The study revealed that most of the participants in the study highly appreciated the effectiveness of using mobile apps in their learning. Furthermore, the students were critical in selecting the appropriate apps that suit them and their learning purposes. Based on the study, the researcher found out the top five prevalent apps that students frequently used including English Grammar Test, Duolinggo, Busuu, kamusku and English Listening and Speaking. The criteria of choosing the apps are ranging from tha app relevant to students’ need, the user-friendly app, the free of cost app, and the app with gamification features.